2010
DOI: 10.1111/j.1460-9568.2010.07206.x
|View full text |Cite
|
Sign up to set email alerts
|

Semantic confusion regarding the development of multisensory integration: a practical solution

Abstract: There is now a good deal of data from neurophysiological studies in animals and behavioral studies in human infants regarding the development of multisensory processing capabilities. Although the conclusions drawn from these different datasets sometimes appear to conflict, many of the differences are due to the use of different terms to mean the same thing and, more problematic, the use of similar terms to mean different things. Semantic issues are pervasive in the field and complicate communication among grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
93
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(98 citation statements)
references
References 32 publications
(58 reference statements)
1
93
1
3
Order By: Relevance
“…However, other studies have found that adolescents with ASD catch up to their typically developing peers and that these deficits are ameliorated upon entering adolescence (39,40). Also the terminology of "multisensory integration" is inconsistent (28,41), making the interpretation of results complex. Thus, a second goal of the present study was to test for a specific, well-studied property of cue combination.…”
Section: Significancementioning
confidence: 99%
“…However, other studies have found that adolescents with ASD catch up to their typically developing peers and that these deficits are ameliorated upon entering adolescence (39,40). Also the terminology of "multisensory integration" is inconsistent (28,41), making the interpretation of results complex. Thus, a second goal of the present study was to test for a specific, well-studied property of cue combination.…”
Section: Significancementioning
confidence: 99%
“…Note that we follow the terminology suggested by Stein et al (2010) by using "cross-modal" when referring to the stimulus complex or the experimental condition and "multisensory" when referring to the (observed) biological consequences. The auditory (A) and visual (V) stimuli were delivered modality specific, or in combination (cross-modal, AV).…”
Section: Methodsmentioning
confidence: 99%
“…Stein et al 2010). Previous event-related potential (ERP) studies in young adults showed that sensory-specific regions, namely primary auditory, primary visual, ventral occipito-temporal and superior temporal cortices displayed increased activity in response to temporally-and semantically-congruent cross-modal inputs (Cappe, Thut, Romei & Murray, 2010;Raij et al, 2010;Teder-Sälejärvi, Russo, McDonald & Hillyard, 2005).…”
Section: Introductionmentioning
confidence: 99%